ANALISIS TINGKAT LITERASI KEUANGAN PADA USAHA MIKRO DI KOTA KENDARI SULAWESI TENGGARA - Christofel Filemon Dirman; Muhammad Natsir; Irmawatty Paula Tamburaka (Universitas Halu Oleo, 2021)
The purpose of this study is to determine the level of financial literacy in micro enterprises that are actively running their business in Paddy's Market, Korem Side Market, and Kendari City's Anduonohu Market. This technique is used because the population is high and not homogeneous, and also proportionally stratified. The data collection technique used was questionnaire data which would be distributed to respondents. The method used is a qualitative descriptive analysis method with field data analysis based on 15 financial literacy indicators used by (Widayati, 2012), and also based on the levels used by the Financial Services Authority (OJK), namely: well literate, sufficient literate, less literate and not literate. The results of this study indicate that the level of financial literacy of micro-business traders in the three markets in Kendari city, namely Paddy's Market, Korem Side Market, Anduonohu Market is in the less literate category based on the level of knowledge and skills possessed. This is due to a lack of knowledge in managing finances, financial service products as well as a lack of education level and monthly income earned by micro-entrepreneurs while they are still actively doing business in Paddy's market, Korem side market, and Anduonohu market.